1990
DOI: 10.1177/074823379000600110
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function, Airway Responsiveness, and Respiratory Symptoms in Asthmatics Following Exercise in No2

Abstract: Two experiments were conducted to determine respiratory responses of persons with asthma performing intermittent moderate exercise while exposed to low concentrations of NO2. In the first, preliminary experiment, 13 male subjects, aged 19-35, with mild asthma were exposed on separate days in a chamber (natural breathing, 20 degrees C, 40% RH) to 0.30 ppm NO2 and to a control or "clean air" exposure (0.0 ppm NO2). Exposure included three 10-min periods of moderate treadmill exercise (VE = 44.5 liter/min), each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 15 publications
1
19
1
Order By: Relevance
“…EVects of the single substance on lung function and bronchial responsiveness were shown at concentrations above 1 ppm NO 2 in healthy persons (Blomberg et al , 1997Bylin 1993;Frampton 1991;Mohsenin 1988) and above 0.1-0.25 ppm in asthmatics (Folinsbee et al 1992;Strand et al 1996Strand et al , 1998Roger et al 1990) as well as COPD patients (Morrow et al 1992). In a previous study (Frampton et al 1989) it was found that alveolar macrophages obtained from healthy subjects by broncho-alveolar lavage when exposed to 0.60 ppm NO 2 for 3 h were less eVective when inactivating inXuenza virus in vitro as compared with alveolar macrophages obtained after air exposure.…”
Section: Results Of the Longitudinal Investigations In Mine A And Bmentioning
confidence: 99%
“…EVects of the single substance on lung function and bronchial responsiveness were shown at concentrations above 1 ppm NO 2 in healthy persons (Blomberg et al , 1997Bylin 1993;Frampton 1991;Mohsenin 1988) and above 0.1-0.25 ppm in asthmatics (Folinsbee et al 1992;Strand et al 1996Strand et al , 1998Roger et al 1990) as well as COPD patients (Morrow et al 1992). In a previous study (Frampton et al 1989) it was found that alveolar macrophages obtained from healthy subjects by broncho-alveolar lavage when exposed to 0.60 ppm NO 2 for 3 h were less eVective when inactivating inXuenza virus in vitro as compared with alveolar macrophages obtained after air exposure.…”
Section: Results Of the Longitudinal Investigations In Mine A And Bmentioning
confidence: 99%
“…Animal studies have provided evidence that the particulate fraction of DE is able to cause an increase in airway responsiveness [28], but to the best of the authors9 knowledge, there are no previous experimental data concerning particulate pollution and hyperresponsiveness in humans. Regarding the gaseous phase of DE, some studies have reported an immediate increase in airway responsiveness following exposure to NO 2 [29,30], whereas other studies have not [31]. Most studies have been designed to explore the immediate and early effects of NO 2 and it is not clear from the literature whether NO 2 is able to induce a sustained increase in airway responsiveness.…”
Section: Discussionmentioning
confidence: 96%
“…In asthmatics, the data on nonspecific hyperresponsiveness to NO 2 suggests a sensitizing effect between 0.2 ppm and 0.6 ppm, though the responses, where significant, were small and unlikely to be of clinical significance (Bylin et al, 1985;Mohsenin, 1987;Strand et al, 1996). A limited number of studies have evaluated airway hyperresponsiveness in asthmatics at multiple NO 2 concentrations, and the results of these studies do not support a clear concentration-response relationship between 0.1 ppm and 0.5ppm (Bylin et al, 1988;Roger et al, 1990;Tunnicliffe, Burge & Ayres, 1994). It should be noted that, in all of the studies cited, a range of responses were observed; and in many studies, subgroups of responders were identified.…”
Section: Chamber Studiesmentioning
confidence: 94%